The Contribution of Ragunan Fern Data to the Indonesian Urban Pteridology Studies - Ulfa, Erlandy; Wardhani, Wita; Sedayu, Agung (Proceeding International Conference on Global Resource Conservation, 2013)
Ragunan Zoo is among few large green areas in Jakarta where the natural local flora remains, including ferns, are capable to proliferate according to habitat availability. We performed a pteridology survey in Ragunan and found 21 fern species, most of which was free living species, not cultivated species. In fact, the highest importance values were held entirely by free living species, Amphineuron terminans (Thelypteridaceae; 32.93), followed by Sphaerostephanos appendiculata (Thelypteridaceae; 27.70), Nephrolepis biserrata (Lomariopsidaceae; 26.63), and Adiantum tenerum (Adiantaceae; 22.01). The Shannon-Wiener diversity index for Ragunan ferns was 2.39 (high-moderate). When compared to other urban and conservational areas (using existing literatures), Ragunan fern species number is within range of average species number curve constructed by both areas. We believe in ferns, the anemochorous spore dispersal mode and the capability of long range dispersal are very important, thus expanding the recruitment and establishment rate in urban habitats, especially those less-managed, comparable with those in conservational areas. Â Key words: conservational area, ferns, spore dispersal, urban habitat